Positive electrode for all-solid-state battery and all-solid-state battery

By forming a reaction suppression layer on the surface of the positive active material of all solid-state batteries and adjusting its diameter ratio to the solid-state electrolytic particles, the problem of insufficient load characteristics is solved, and better load characteristics and battery performance is achieved.

JP7657576B2Active Publication Date: 2025-04-07MAXELL LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020194842
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-11-25
Publication Date
2025-04-07
Estimated Expiration
2040-11-25

Smart Images

  • Figure 0007657576000002
    Figure 0007657576000002
  • Figure 0007657576000003
    Figure 0007657576000003
  • Figure 0007657576000004
    Figure 0007657576000004
Patent Text Reader

Abstract

To provide an all-solid-state battery having excellent load characteristics and a positive electrode capable of forming the all-solid-state battery, and relate to goals 12, 3, 7, and 11 of sustainable development goals (SDGs).SOLUTION: A positive electrode for an all-solid battery according to the present invention includes a positive electrode active material composed of primary particles and a molded body of a positive electrode mixture containing a solid electrolyte, and the positive electrode active material includes a reaction suppression layer for suppressing the reaction on the positive electrode active material and the solid electrolyte layer, and the ratio ra / rs of the average particle size ra of the positive electrode active material to the average particle size rs of the solid electrolyte is 2 or more and 20 or less. Further, an all-solid-state battery according to the present invention includes a positive electrode, a negative electrode, and a solid electrolyte layer interposed between the positive electrode and the negative electrode, and includes the positive electrode for the all-solid-state battery according to the present invention.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an all-solid-state battery having excellent load characteristics and a positive electrode capable of constituting the all-solid-state battery. [Background technology]

[0002] In recent years, with the development of portable electronic devices such as mobile phones and notebook personal computers, and the practical application of electric vehicles, there has been a demand for small, lightweight batteries with high capacity and high energy density.

[0003] Currently, lithium batteries, particularly lithium ion batteries, capable of meeting this demand use an organic electrolyte solution containing an organic solvent and a lithium salt as the non-aqueous electrolyte.

[0004] Furthermore, with the further development of devices in which lithium-ion batteries are used, there is a demand for longer life, higher capacity, and higher energy density of lithium-ion batteries. At the same time, there is also a high demand for the reliability of lithium-ion batteries with longer life, higher capacity, and higher energy density.

[0005] However, the organic electrolyte used in lithium-ion batteries contains an organic solvent, which is a flammable substance, and therefore the organic electrolyte may generate abnormal heat when an abnormality such as a short circuit occurs in the battery. In addition, with the recent trend toward higher energy density of lithium-ion batteries and an increasing amount of organic solvent in the organic electrolyte, there is a demand for even higher reliability in lithium-ion batteries.

[0006] In the above circumstances, all-solid-state lithium batteries that do not use organic solvents (all-solid-state batteries) are attracting attention. All-solid-state batteries use a molded body of a solid electrolyte that does not use an organic solvent instead of the conventional organic solvent-based electrolyte, and are highly safe without the risk of abnormal heat generation of the solid electrolyte.

[0007] In addition, all-solid-state batteries are not only highly safe, but also highly reliable, highly environmentally resistant, and have a long lifespan, so they are expected to be maintenance-free batteries that can contribute to social development while also continuing to contribute to safety and security. By providing all-solid-state batteries to society, we can contribute to the achievement of Goal 12 (Ensure sustainable consumption and production patterns), Goal 3 (Ensure healthy lives and promote well-being for all at all ages), Goal 7 (Ensure access to affordable, reliable, sustainable and modern energy for all), and Goal 11 (Make cities and human settlements inclusive, safe, resilient and sustainable) out of the 17 goals of the Sustainable Development Goals (SDGs) established by the United Nations.

[0008] In addition, various improvements have been attempted for all-solid-state batteries. For example, Patent Document 1 proposes a technique for increasing the utilization rate of active materials in all-solid-state batteries by applying an electrode using a mixture of an active material having a specific particle size and a solid electrolyte having a specific particle size in a specific weight ratio.

[0009] Furthermore, Patent Document 2 proposes a technology for reducing the interfacial resistance between a positive electrode active material layer or a negative electrode active material layer and a solid electrolyte layer by setting the ratio of the particle size of the positive electrode active material in a positive electrode active material layer of a positive electrode layer or the particle size of the negative electrode active material in a negative electrode active material layer of a negative electrode layer, to the particle size of the solid electrolyte in a solid electrolyte layer adjacent to these layers, within a specific range. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Japanese Patent Application Publication No. 8-195219 [Patent Document 2] JP 2016-1596 A Summary of the Invention [Problem to be solved by the invention]

[0011] Incidentally, the fields of application of all-solid-state batteries are currently expanding rapidly. For example, applications requiring discharge at a large current value are expected. Therefore, there is a demand for improving the load characteristics so as to meet these applications.

[0012] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide an all-solid-state battery having excellent load characteristics and a positive electrode capable of constituting the all-solid-state battery. [Means for solving the problem]

[0013] The positive electrode for an all-solid-state battery of the present invention comprises a molded body of a positive electrode mixture containing a positive electrode active material composed of primary particles and a solid electrolyte, the positive electrode active material having a reaction suppression layer on a surface thereof for suppressing a reaction between the positive electrode active material and the solid electrolyte, and a ratio ra / rs of an average particle diameter ra of the positive electrode active material to an average particle diameter rs of the solid electrolyte being 2 or more and 20 or less.

[0014] The all-solid-state battery of the present invention has a positive electrode, a negative electrode, and a solid electrolyte layer interposed between the positive electrode and the negative electrode, and is characterized in that the positive electrode is the positive electrode for an all-solid-state battery of the present invention.

[0015] The all-solid-state battery of the present invention includes a primary battery (all-solid-state primary battery) and a secondary battery (all-solid-state secondary battery). Effect of the Invention

[0016] According to the present invention, it is possible to provide an all-solid-state battery having excellent load characteristics and a positive electrode capable of constituting the all-solid-state battery. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a cross-sectional view illustrating a schematic diagram of an example of an all-solid-state battery of the present invention. [Diagram 2] FIG. 2 is a plan view illustrating another example of the all-solid-state battery of the present invention. [Diagram 3] 2. FIG. 2 is a cross-sectional view taken along line II in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] <Cathode for all-solid-state batteries> The positive electrode for an all-solid-state battery of the present invention has a molded body of a positive electrode mixture containing a positive electrode active material composed of primary particles and a solid electrolyte, the positive electrode active material has a reaction suppression layer on a surface thereof for suppressing a reaction between the positive electrode active material and the solid electrolyte, and a ratio ra / rs of an average particle diameter ra of the positive electrode active material to an average particle diameter rs of the solid electrolyte is 2 or more and 20 or less.

[0019] In order to improve the load characteristics of an all-solid-state battery, it is desirable to enable lithium ions to move more smoothly between the positive electrode active material and the solid electrolyte in the positive electrode.

[0020] In the present invention, in a molded body of a positive electrode mixture constituting a positive electrode, a positive electrode active material having a reaction suppression layer on its surface for suppressing reaction with a solid electrolyte is contained in the form of primary particles, and the ratio of the average particle size of the positive electrode active material to the average particle size of the solid electrolyte is set within a specific range, thereby improving contact between the positive electrode active material and the solid electrolyte and enabling smooth movement of lithium ions between the two, thereby improving the load characteristics of the all-solid-state battery.

[0021] The positive electrode for an all-solid-state battery of the present invention has a molded body of a positive electrode mixture, and examples thereof include one consisting of a molded body of a positive electrode mixture alone and one having a structure in which a layer (positive electrode mixture layer) consisting of a molded body of a positive electrode mixture is formed on a current collector.

[0022] In the case of a positive electrode for an all-solid-state battery used in an all-solid-state primary battery, the base material of the positive electrode active material (positive electrode active material having a reaction suppression layer on its surface) to be contained in the positive electrode mixture can be the same as the positive electrode active material used in conventionally known non-aqueous electrolyte primary batteries. Specifically, for example, manganese dioxide, lithium-containing manganese oxide [e.g., LiMn 3 O 6or a composite oxide having the same crystal structure as manganese dioxide (such as β-type, γ-type, or a structure in which β-type and γ-type are mixed), and having a Li content of 3.5% by mass or less, preferably 2% by mass or less, more preferably 1.5% by mass or less, particularly preferably 1% by mass or less), Li a Ti 5 / 3 O 4 (4 / 3 ≦ a < 7 / 3) and other lithium-containing composite oxides; vanadium oxides; niobium oxides; titanium oxides; sulfides such as iron disulfide; graphite fluoride; Ag 2 silver sulfides such as S; NiO 2 and other nickel oxides: and the like.

[0023] In the case of a positive electrode for an all-solid-state secondary battery used in an all-solid-state secondary battery, as the base material of the positive electrode active material (positive electrode active material having a reaction suppression layer on the surface) contained in the positive electrode mixture, the same positive electrode active materials as those conventionally used in non-aqueous electrolyte secondary batteries can be used, that is, active materials capable of occluding and releasing Li (lithium) ions. Specifically, Li 1-x M r Mn 2-r O 4 (where M is at least one element selected from the group consisting of Li, Na, K, B, Mg, Ca, Sr, Ba, Ti, V, Cr, Zr, Fe, Co, Ni, Cu, Zn, Al, Sn, Sb, In, Nb, Ta, Mo, W, Y, Ru, and Rh, 0 ≦ x ≦ 1, 0 ≦ r ≦ 1) spinel-type lithium manganese composite oxide represented by, Li r Mn (1-s-t) Ni s M t O (2-u) F v (where M is at least one element selected from the group consisting of Co, Mg, Al, B, Ti, V, Cr, Fe, Cu, Zn, Zr, Mo, Sn, Ca, Sr, and W, 0 ≦ r ≦ 1.2, 0 < s < 0.5, 0 ≦ t ≦ 0.5, u + v < 1, -0.1 ≦ u ≦ 0.2, 0 ≦ v ≦ 0.1) layered compound represented by, Li 1-x Co 1-r M r O 2(wherein M is at least one element selected from the group consisting of Al, Mg, Ti, V, Cr, Zr, Fe, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb, Ba, Mn, Bi, Ca, F, P, Sr, W, Si, Ta, K, S, Er, and Na, and 0≦x≦1, 0≦r≦0.5), lithium cobalt composite oxide represented by the formula: 1-x Ni 1-r M r O 2 (wherein M is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Fe, Co, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb, and Ba, and 0≦x≦1, 0≦r≦0.5), lithium nickel composite oxide represented by Li 1+s-x M 1-r N r PO 4 F s (wherein M is at least one element selected from the group consisting of Fe, Mn, and Co, and N is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb, V, and Ba, and 0≦x≦1, 0≦r≦0.5, and 0≦s≦1), Li 2-x M 1-r N r P 2 O 7 (wherein M is at least one element selected from the group consisting of Fe, Mn, and Co, and N is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb, V, and Ba, and 0≦x≦2, 0≦r≦0.5), and the like can be exemplified. Among these, only one type may be used, or two or more types may be used in combination.

[0024] In the case of a positive electrode for an all-solid-state battery used in an all-solid-state secondary battery, among the above-exemplified positive electrode active materials, a lithium-cobalt composite oxide (A) represented by the following general formula (1) is preferably used.

[0025] LiCo 1-a-b-c Al a M1 b M 2 c O 2 (1)

[0026] In the general formula (1), M 1 represents at least one element selected from the group consisting of Mg, Ni and Na; M 2 is at least one element selected from the group consisting of Mn, Fe, Cu, Zr, Ti, Bi, Ca, F, P, Sr, W, Ba, Nb, Si, Zn, Mo, V, Sn, Sb, Ta, Ge, Cr, K, S, and Er, and 0 <a<0.1、0<b<0.1、a+b<0.1、0≦cである。

[0027] When the lithium cobalt composite oxide (A) is used as a positive electrode active material for a non-aqueous electrolyte secondary battery using an organic electrolyte, the Al and M contained therein are 1 Lithium-cobalt composite oxide (A) is a material that increases the internal resistance of a battery by the action of an additive element such as lithium-ion-containing elements. However, in the case of a non-aqueous electrolyte secondary battery having an organic electrolyte, the electrolyte that transfers ions between the positive and negative electrodes is liquid (electrolytic solution), and therefore the original internal resistance is small, so the increase in internal resistance due to the lithium-cobalt composite oxide (A) has almost no effect on the battery characteristics. On the other hand, in an all-solid-state secondary battery in which ions are transferred between the positive and negative electrodes by a solid electrolyte, it is expected that the increase in internal resistance due to the action of the positive electrode active material will cause a decrease in battery characteristics such as load characteristics.

[0028] However, contrary to these expectations, when the lithium-cobalt composite oxide (A) is used as a positive electrode active material for an all-solid-state secondary battery, for example, LiCoO 2 In comparison with the case where a cathode active material is used, it is possible to reduce the internal resistance, and the load characteristics of the all-solid-state secondary battery can be further improved.

[0029] LiCoO 2When a battery using Co as the positive electrode active material is charged, the Co expands due to a change in valence. In a battery using an organic electrolyte, even if the volume of the positive electrode active material changes due to this, the electrolyte that transfers ions is liquid, so contact with the positive electrode active material is not lost. On the other hand, in an all-solid-state secondary battery, the electrolyte that transfers ions in the positive electrode is solid (solid electrolyte), so the volume of the positive electrode active material changes when the battery is charged and discharged, creating a gap between the solid electrolyte, and the internal resistance of the positive electrode and, ultimately, the battery increases.

[0030] However, in the case of the lithium cobalt composite oxide (A) represented by the general formula (1), even in a charged state, Al and the element M 1 Since the expansion of Co is suppressed by this action, the amount of expansion (volume change) of the entire positive electrode active material is small. Therefore, by using a positive electrode for an all-solid-state battery that uses the lithium cobalt composite oxide (A) as the positive electrode active material, good contact between the lithium cobalt composite oxide (A) and the solid electrolyte in the positive electrode can be maintained even during charging and discharging, and the internal resistance can be kept low, resulting in an all-solid-state secondary battery with better load characteristics.

[0031] In the lithium cobalt composite oxide (A), Al is an element that substitutes for the Co site, M 1 are elements that are substituted for the Li site, and both have the effect of reducing the amount of expansion of Co (the amount of expansion of the lithium cobalt composite oxide (A)) during charging.

[0032] Lithium cobalt composite oxide (A) contains element M 1 At least one element selected from Mg, Ni, and Na may be contained as the lithium ion species. However, Mg is preferred since it has an ionic radius equivalent to that of the Li which it substitutes, and furthermore does not undergo a change in valence during charging and discharging.

[0033] In the lithium cobalt composite oxide (A), in order to suppress the expansion amount during charging, the amount of Al, a, is greater than 0 and less than 0.1, and the amount of element M 1The amount b of Al is greater than 0 and less than 0.1, and a+b is less than 0.1. The amount a of Al is preferably 0.005 or more, and the amount of element M 1 The amount b of element M is preferably 0.005 or more. Furthermore, the amount a of Al is preferably 0.08 or less. 1 The amount b is preferably 0.08 or less.

[0034] Lithium cobalt composite oxide (A) contains element M 2 may or may not be contained (the amount c may be 0), but element M 2 If the amount of element M is too large, for example, the amount of Co may become small, and the capacity of the lithium cobalt composite oxide (A) may become small. 2 The amount c is preferably 0.05 or less.

[0035] The positive electrode mixture compact contains the positive electrode active material in the form of primary particles, which improves the contact between the positive electrode active material in the positive electrode mixture compact and the solid electrolyte, thereby improving the load characteristics of the all-solid-state battery.

[0036] The molded body of the positive electrode mixture may contain a positive electrode active material existing as secondary particles together with a positive electrode active material consisting of primary particles. Examples of the positive electrode active material existing as secondary particles include secondary particles of various positive electrode active materials exemplified above as materials that can be contained in the positive electrode mixture. However, the proportion of the positive electrode active material existing as secondary particles in the positive electrode mixture in the total amount of the positive electrode active material is preferably as small as possible, and is preferably 20% by mass or less, and more preferably 10% by mass or less. In addition, the positive electrode active material in the positive electrode mixture may be a positive electrode active material consisting entirely of primary particles. Therefore, the lower limit of the proportion of the positive electrode active material existing as secondary particles in the total amount of the positive electrode active material is 0% by mass.

[0037] As the positive electrode active material made of primary particles, a commercially available positive electrode active material can be used. It is also possible to use a positive electrode active material that contains some secondary particles but is mostly made of primary particles.

[0038] The positive electrode active material (positive electrode active material made of primary particles) contained in the positive electrode mixture compact has a reaction suppression layer on its surface for suppressing reaction with the solid electrolyte contained in the positive electrode.

[0039] If the positive electrode active material and the solid electrolyte come into direct contact with each other in the positive electrode mixture compact, the solid electrolyte may oxidize to form a resistance layer, which may reduce the ionic conductivity in the compact. By providing a reaction suppression layer that suppresses the reaction with the solid electrolyte on the surface of the positive electrode active material and preventing direct contact between the positive electrode active material and the solid electrolyte, it is possible to suppress the reduction in the ionic conductivity in the compact due to the oxidation of the solid electrolyte.

[0040] The reaction suppression layer may be made of a material that has ion conductivity and can suppress the reaction between the positive electrode active material and the solid electrolyte. Examples of materials that can form the reaction suppression layer include oxides containing Li and at least one element selected from the group consisting of Nb, P, B, Si, Ge, Ti, and Zr, more specifically, LiNbO 3 Nb-containing oxides such as Li 3 PO 4 , Li 3 BO 3 , Li 4 SiO 4 , Li 4 GeO 4 , LiTiO 3 , LiZrO 3 , Li 2 WO 4 The reaction suppression layer may contain only one of these oxides, or may contain two or more of these oxides, or may contain a composite compound of two or more of these oxides. Among these oxides, it is preferable to use an Nb-containing oxide, and LiNbO 3 It is more preferable to use

[0041] The reaction suppression layer is preferably present on the surface in an amount of 0.1 to 1.0 part by mass per 100 parts by mass of the positive electrode active material, in order to effectively suppress the reaction between the positive electrode active material and the solid electrolyte.

[0042] Methods for forming a reaction suppression layer on the surface of a positive electrode active material include the sol-gel method, mechanofusion method, CVD method, PVD method, and ALD method.

[0043] In addition, when the molded body of the positive electrode mixture also contains a positive electrode active material existing as secondary particles, it is preferable that the positive electrode active material existing as secondary particles (primary particles of the positive electrode active material constituting the secondary particles) also have the above-mentioned reaction suppression layer.

[0044] The content of the positive electrode active material in the positive electrode mixture is preferably 60 to 95 mass %.

[0045] The solid electrolyte to be contained in the positive electrode mixture compact is not particularly limited as long as it has lithium ion conductivity. For example, a sulfide-based solid electrolyte, a hydride-based solid electrolyte, a halide-based solid electrolyte, an oxide-based solid electrolyte, etc. can be used.

[0046] As for sulfide-based solid electrolytes, Li 2 SP 2 S 5 , Li 2 S-SiS 2 , Li 2 SP 2 S 5 -GeS 2 , Li 2 S.B. 2 S 3 In addition to particles such as thio-LISICON type particles, which have been attracting attention in recent years for their high Li-ion conductivity, 10 GeP 2 S 12 , Li 9.54 S 1.74 P 1.44 S 11.7 Cl 0.3 Li 12-12a-b+c+6d-e M 1 3+a-b-c-d M 2 b M 3 c M 4d M 5 12-e X e (However, M 1 is Si, Ge or Sn, M 2 is P or V, M 3 is Al, Ga, Y or Sb, M 4 is Zn, Ca, or Ba, M 5 is either S or S and O, X is F, Cl, Br or I, 0 ≦ a < 3, 0 ≦ b + c + d ≦ 3, 0 ≦ e ≦ 3), or those of the al-diolite type [Li 6 PS 5 Cl, etc., Li 7-f+g PS 6-x Cl x+y (However, 0.05 ≦ f ≦ 0.9, -3.0f + 1.8 ≦ g ≦ -3.0f + 5.7), Li 7-h PS 6-h Cl i Br j (However, h = i + j, 0 < h ≦ 1.8, 0.1 ≦ i / j ≦ 10.0), etc.] can also be used.

[0047] Examples of the hydride-based solid electrolyte include, for example, LiBH 4 , LiBH 4 and a solid solution with the following alkali metal compound (for example, those with a molar ratio of LiBH 4 to the alkali metal compound of 1:1 to 20:1), etc. Examples of the alkali metal compound in the solid solution include at least one selected from the group consisting of lithium halides (LiI, LiBr, LiF, LiCl, etc.), rubidium halides (RbI, RbBr, RbF, RbCl, etc.), cesium halides (CsI, CsBr, CsF, CsCl, etc.), lithium amide, rubidium amide, and cesium amide.

[0048] Examples of the halide-based solid electrolyte include, for example, monoclinic LiAlCl 4 , defective spinel-type or layered-structured LiInBr 4 , monoclinic Li 6-3m Y m X 6(However, 0 < m < 2 and X = Cl or Br), etc. can be mentioned, and in addition, for example, those known in International Publication No. 2020 / 070958 and International Publication No. 2020 / 070955 can be used.

[0049] As the oxide-based solid electrolyte, for example, garnet-type Li 7 La 3 Zr 2 O 12 , NASICON-type Li 1+O Al 1+O Ti 2-O (PO 4 ) 3 , Li 1+p Al 1+p Ge 2-p (PO 4 ) 3 , perovskite-type Li 3q La 2 / 3-q TiO 3 and the like can be mentioned.

[0050] Among these solid electrolytes, sulfide-based solid electrolytes are preferred because of their high lithium ion conductivity, sulfide-based solid electrolytes containing Li and P are more preferred, and particularly, argyrodite-type sulfide-based solid electrolytes with high lithium ion conductivity and high chemical stability are even more preferred.

[0051] The content of the solid electrolyte in the positive electrode mixture is preferably 4 to 40% by mass.

[0052] When the average particle diameter of the solid electrolyte contained in the compact of the positive electrode mixture is rs (μm) and the average particle diameter of the positive electrode active material consisting of primary particles contained in the compact of the positive electrode mixture is ra (μm), the ratio of ra to rs, ra / rs, is 2 or more and 20 or less. When the value of ra / rs is within the above range, the contact between the positive electrode active material and the solid electrolyte in the compact of the positive electrode mixture is good, and ions can move smoothly between them, so that the resistance value of the positive electrode for the all-solid-state battery can be reduced and the load characteristics of the all-solid-state battery (the all-solid-state battery of the present invention) in which this positive electrode is used can be improved. The value of ra / rs is more preferably 5 or more and more preferably 15 or less.

[0053] The average particle size of the solid electrolyte is preferably 0.4 μm or more and 2.5 μm or less.

[0054] Furthermore, the average particle size of the positive electrode active material consisting of primary particles is preferably 2 μm or more, more preferably 5 μm or more, and is preferably 30 μm or less, more preferably 10 μm or less.

[0055] In addition, when the positive electrode mixture compact contains a positive electrode active material that exists in the state of secondary particles, the average particle diameter of the secondary particles is preferably approximately equal to the average particle diameter of the positive electrode active material consisting of primary particles.

[0056] The average particle diameter of various particles (positive electrode active material, solid electrolyte, etc.) in this specification is the 50% diameter value (D) in the volume-based integrated fraction when calculating the integral volume from small particles using a particle size distribution measurement device (such as the Microtrac particle size distribution measurement device "HRA9320" manufactured by Nikkiso Co., Ltd.). 50 )

[0057] The average particle diameter of the positive electrode active material or the solid electrolyte can also be determined by observing the surface of the positive electrode mixture compact with a scanning electron microscope (SEM) and averaging (number average) all values ​​of particle diameters measured using the SEM scale for a specific number (e.g., 30 pieces) of positive electrode active material or solid electrolyte. The present inventors have confirmed that the average particle diameter of the positive electrode active material and the average particle diameter of the solid electrolyte determined by this method are substantially equivalent to the average particle diameter of the positive electrode active material and the average particle diameter of the solid electrolyte determined by using the particle size distribution measuring device.

[0058] The positive electrode mixture compact may contain a conductive assistant. Specific examples of the conductive assistant include carbon materials such as graphite (natural graphite, artificial graphite), graphene, carbon black, carbon nanofiber, and carbon nanotubes. For example, Ag may be used as the positive electrode active material. 2 When S is used, since Ag having electrical conductivity is generated during the discharge reaction, it is not necessary to add a conductive auxiliary. When a conductive auxiliary is added to the positive electrode mixture compact, the content of the conductive auxiliary in the positive electrode mixture is preferably 1 to 10 mass %.

[0059] The molded body of the positive electrode mixture may or may not contain a resin binder. Examples of the resin binder include fluororesins such as polyvinylidene fluoride (PVDF). However, since the resin binder acts as a resistance component in the molded body of the positive electrode mixture, it is desirable that the amount of the resin binder is as small as possible. Therefore, in the molded body of the positive electrode mixture, it is preferable that the resin binder is not contained, or if it is contained, the content in the positive electrode mixture is 0.5 mass% or less. The content of the resin binder in the positive electrode mixture is more preferably 0.3 mass% or less, and even more preferably 0 mass% (i.e., no resin binder is contained).

[0060] When a current collector is used for the positive electrode, the current collector can be made of a metal foil such as aluminum or stainless steel, a punched metal, a net, an expanded metal, a foamed metal, a carbon sheet, or the like.

[0061] The positive electrode mixture compact can be formed, for example, by compressing a positive electrode mixture prepared by mixing a positive electrode active material with a conductive assistant, a binder, a solid electrolyte, and the like, which are added as necessary, by pressure molding or the like.

[0062] In the case of a positive electrode having a current collector, the positive electrode can be produced by bonding a molded body of the positive electrode mixture formed by the above-mentioned method to the current collector by, for example, pressure bonding.

[0063] Alternatively, the positive electrode mixture may be mixed with a solvent to prepare a positive electrode mixture-containing composition, which may then be applied onto a substrate such as a current collector or a solid electrolyte layer (in the case of forming a solid electrolyte battery) that faces the positive electrode, dried, and then pressed to form a molded body of the positive electrode mixture.

[0064] The solvent for the positive electrode mixture-containing composition may be an organic solvent such as water or N-methyl-2-pyrrolidone (NMP). When the positive electrode mixture-containing composition also contains a solid electrolyte, it is preferable to select a solvent that does not easily deteriorate the solid electrolyte. In particular, since sulfide-based solid electrolytes and hydride-based solid electrolytes undergo chemical reactions due to a small amount of water, it is preferable to use a non-polar aprotic solvent represented by a hydrocarbon solvent such as hexane, heptane, octane, nonane, decane, decalin, toluene, or xylene. In particular, it is more preferable to use an ultra-dehydrated solvent with a water content of 0.001 mass% (10 ppm) or less. In addition, fluorine-based solvents such as "Vertrel (registered trademark)" manufactured by Mitsui DuPont Fluorochemicals, "Zeorolla (registered trademark)" manufactured by Nippon Zeon Co., Ltd., and "Novec (registered trademark)" manufactured by Sumitomo 3M Co., Ltd., as well as non-aqueous organic solvents such as dichloromethane and diethyl ether can also be used.

[0065] The thickness of the positive electrode mixture compact (in the case of an electrode having a current collector, the thickness of the positive electrode mixture compact per one side of the current collector; the same applies below) is usually 50 μm or more, but from the viewpoint of increasing the capacity of the battery, it is preferably 200 μm or more. Also, the thickness of the positive electrode mixture compact is usually 3000 μm or less.

[0066] In the case of a positive electrode produced by forming a positive electrode mixture layer made of a compact of a positive electrode mixture on a current collector using a positive electrode mixture-containing composition containing a solvent, the thickness of the positive electrode mixture layer is preferably 50 to 1000 μm.

[0067] <All-solid-state battery> The all-solid-state battery of the present invention has a positive electrode, a negative electrode, and a solid electrolyte layer interposed between the positive electrode and the negative electrode, and the positive electrode is the positive electrode for the all-solid-state battery of the present invention.

[0068] (Negative electrode) The negative electrode of the all-solid-state battery can have, for example, a molded body of a negative electrode mixture containing a negative electrode active material and a solid electrolyte, and can be made of only a molded body of a negative electrode mixture, or a structure in which a layer (negative electrode mixture layer) made of a molded body of a negative electrode mixture is formed on a current collector.

[0069] When the all-solid-state battery is a primary battery, examples of the negative electrode active material include metallic lithium and lithium alloys (lithium-aluminum alloys).

[0070] Furthermore, in the case where the all-solid-state battery is a secondary battery, examples of the negative electrode active material include metallic lithium, lithium alloys (lithium-aluminum alloys), and the like, as well as carbon materials such as graphite, pyrolytic carbons, cokes, glassy carbon, fired bodies of organic polymer compounds, mesocarbon microbeads, carbon fibers, and activated carbon; alloys containing elements that can be alloyed with lithium, such as Si and Sn; and oxides of Si and Sn.

[0071] The content of the negative electrode active material in the negative electrode mixture is preferably 40 to 95 mass %.

[0072] The negative electrode mixture compact contains a solid electrolyte. Specific examples thereof include the same solid electrolytes as those exemplified above as those that can be contained in the positive electrode mixture compact. Among the above-mentioned solid electrolytes, it is more preferable to use a sulfide-based solid electrolyte because it has high lithium ion conductivity and has a function of increasing the moldability of the negative electrode mixture.

[0073] The content of the solid electrolyte in the negative electrode mixture is preferably 4 to 49 mass %.

[0074] The negative electrode mixture compact may contain a conductive assistant. Specific examples thereof include the same conductive assistants as those exemplified above as those that may be contained in the positive electrode mixture compact. The content of the conductive assistant in the negative electrode mixture is preferably 1 to 10 mass%.

[0075] In addition, the molded body of the negative electrode mixture may or may not contain a resin binder. Examples of the resin binder include fluororesins such as polyvinylidene fluoride (PVDF). However, since the resin binder acts as a resistance component even in the molded body of the negative electrode mixture, it is desirable that the amount of the resin binder is as small as possible. Therefore, in the molded body of the negative electrode mixture, it is preferable that the resin binder is not contained, or if it is contained, the content in the negative electrode mixture is 0.5 mass% or less. The content of the resin binder in the negative electrode mixture is more preferably 0.3 mass% or less, and even more preferably 0 mass% (i.e., no resin binder is contained).

[0076] When a current collector is used in a negative electrode having a molded body of a negative electrode mixture, the current collector can be made of copper or nickel foil, punched metal, net, expanded metal, foamed metal; carbon sheet; or the like.

[0077] The negative electrode mixture compact can be formed, for example, by compressing a negative electrode mixture prepared by mixing a negative electrode active material, a solid electrolyte, and further a conductive assistant and a binder, which are added as necessary, by pressure molding, etc. In the case of a negative electrode constituted only by a negative electrode mixture compact, it can be manufactured by the above-mentioned method.

[0078] In the case of a negative electrode having a current collector, the negative electrode can be produced by bonding a molded product of the negative electrode mixture formed by the above-mentioned method to the current collector by, for example, pressure bonding.

[0079] Furthermore, in the case of a negative electrode having a current collector, a negative electrode mixture-containing composition (paste, slurry, etc.) in which a negative electrode active material, a solid electrolyte, and further, if necessary, a conductive assistant and a binder are dispersed in a solvent can also be applied to a current collector, dried, and then, if necessary, pressure-molded by calendaring or the like to form a molded body of the negative electrode mixture (negative electrode mixture layer) on the surface of the current collector.

[0080] As the solvent for the negative electrode mixture-containing composition, an organic solvent such as water or NMP can be used. When the negative electrode mixture-containing composition also contains a solid electrolyte, it is desirable to select a solvent that is unlikely to deteriorate the solid electrolyte. It is preferable to use the same solvent as the various solvents exemplified above as the solvent for the positive electrode mixture-containing composition containing a solid electrolyte.

[0081] The thickness of the negative electrode mixture compact (in the case of a negative electrode having a current collector, the thickness of the negative electrode mixture compact per one side of the current collector; the same applies below) is usually 50 μm or more, but from the viewpoint of increasing the capacity of the battery, it is preferably 200 μm or more. The thickness of the negative electrode mixture compact is usually 3000 μm or less.

[0082] In the case of a negative electrode produced by forming a negative electrode mixture layer made of a molded negative electrode mixture on a current collector using a negative electrode mixture-containing composition containing a solvent, the thickness of the negative electrode mixture layer is preferably 50 to 1000 μm.

[0083] The negative electrode may be made of a metal foil as the negative electrode active material, or may have a structure in which a metal foil as the negative electrode active material and a current collector are laminated.

[0084] In the case of a negative electrode having a structure in which a negative electrode active material and a current collector are laminated, the negative electrode can be obtained, for example, by bonding the metal foil and the current collector together by pressure bonding, etc. In this case, the current collector can be the same as the current collector exemplified above that can be used for a negative electrode having a molded body of a negative electrode mixture.

[0085] In the case of a negative electrode having a metal foil as a negative electrode active material, the negative electrode active material may be metallic lithium or a lithium alloy. Examples of alloying elements in the lithium alloy include aluminum, lead, bismuth, indium, and gallium, with aluminum and indium being preferred. The ratio of alloying elements in the lithium alloy (when multiple alloying elements are included, the total ratio of the alloying elements) is preferably 50 atomic % or less (in this case, the balance is lithium and inevitable impurities).

[0086] In the case of a negative electrode having a lithium alloy foil, a laminate formed by pressing a layer containing an alloying element for forming a lithium alloy on the surface of a lithium layer (a layer containing lithium) composed of a metallic lithium foil or the like is used, and the laminate is brought into contact with a solid electrolyte in a battery to form a lithium alloy on the surface of the lithium layer to form a negative electrode. In the case of such a negative electrode, a laminate having a layer containing an alloying element on only one side of the lithium layer may be used, or a laminate having layers containing an alloying element on both sides of the lithium layer may be used. The laminate can be formed, for example, by pressing a metallic lithium foil and a foil composed of an alloying element.

[0087] The current collector can also be used when a lithium alloy is formed in a battery to form a negative electrode, and for example, a laminate having a lithium layer on one side of the negative electrode current collector and a layer containing an alloying element on the side of the lithium layer opposite the negative electrode current collector may be used, or a laminate having lithium layers on both sides of the negative electrode current collector and each lithium layer having a layer containing an alloying element on the side opposite the negative electrode current collector may be used. The negative electrode current collector and the lithium layer (metallic lithium foil) may be laminated by compression bonding or the like.

[0088] The layer containing the alloying elements in the laminate to be used as the negative electrode may be, for example, a foil composed of these alloying elements. The thickness of the layer containing the alloying elements is preferably 1 μm or more, more preferably 3 μm or more, and is preferably 20 μm or less, more preferably 12 μm or less.

[0089] The lithium layer of the laminate for use as the negative electrode may be, for example, a metallic lithium foil. The thickness of the lithium layer is preferably 0.1 to 1.5 mm. The thickness of the foil for the negative electrode having the metallic lithium foil or lithium alloy foil is also preferably 0.1 to 1.5 mm.

[0090] (Solid electrolyte layer) The solid electrolyte constituting the solid electrolyte layer of the all-solid-state battery can be one or more of the various sulfide-based solid electrolytes, hydride-based solid electrolytes, halide-based solid electrolytes, and oxide-based solid electrolytes exemplified above as those usable for the positive electrode. However, in order to improve the battery characteristics, it is preferable to contain a sulfide-based solid electrolyte, and it is more preferable to contain an Argyrodite-type sulfide-based solid electrolyte. And, it is even more preferable to contain a sulfide-based solid electrolyte in both the positive electrode and the solid electrolyte layer, and also in the negative electrode when the negative electrode is a molded body of a negative electrode mixture containing a solid electrolyte, and it is particularly preferable to contain an Argyrodite-type sulfide-based solid electrolyte.

[0091] The solid electrolyte layer may have a porous body such as a resin nonwoven fabric as a support.

[0092] The solid electrolyte layer can be formed by a method of compressing a solid electrolyte by pressure molding or the like; a method of applying a composition for forming a solid electrolyte layer, which is prepared by dispersing a solid electrolyte in a solvent, onto a substrate, a positive electrode, or a negative electrode, drying the composition, and, if necessary, performing pressure molding such as pressing.

[0093] It is desirable to select a solvent that is unlikely to deteriorate the solid electrolyte as the solvent used in the solid electrolyte layer-forming composition, and it is preferable to use the same solvent as the various solvents exemplified above as the solvent for the positive electrode mixture-containing composition containing the solid electrolyte.

[0094] The thickness of the solid electrolyte layer is preferably 100 to 400 μm.

[0095] (electrode body) The positive electrode and the negative electrode can be used in a battery in the form of a laminated electrode body in which the positive electrode and the negative electrode are laminated with a solid electrolyte layer interposed therebetween, or in the form of a wound electrode body in which this laminated electrode body is wound.

[0096] In forming the electrode body, it is preferable to pressure mold the positive electrode, the negative electrode, and the solid electrolyte layer in a laminated state, from the viewpoint of increasing the mechanical strength of the electrode body.

[0097] (Battery type) A cross-sectional view showing a schematic example of an all-solid-state battery of the present invention is shown in Fig. 1. In the all-solid-state battery 1 shown in Fig. 1, a positive electrode 10 for the all-solid-state battery of the present invention, a negative electrode 20, and a solid electrolyte layer 30 interposed between the positive electrode 10 and the negative electrode 20 are enclosed in an exterior body formed of an exterior can 40, a sealing can 50, and a resin gasket 60 interposed between them.

[0098] The sealing can 50 is fitted into the opening of the outer can 40 via a gasket 60, and the open end of the outer can 40 is tightened inward, whereby the gasket 60 comes into contact with the sealing can 50, sealing the opening of the outer can 40 and forming an airtight structure inside the element.

[0099] The outer can and the sealing can can be made of stainless steel or the like. The gasket can be made of polypropylene, nylon, or the like. If heat resistance is required for the battery's intended use, heat-resistant resins with melting points exceeding 240°C, such as fluororesins such as tetrafluoroethylene-perfluoroalkoxyethylene copolymer (PFA), polyphenylene ether (PEE), polysulfone (PSF), polyarylate (PAR), polyethersulfone (PES), polyphenylene sulfide (PPS), and polyetheretherketone (PEEK), can also be used. If the battery is used in an application requiring heat resistance, a glass hermetic seal can be used for the sealing.

[0100] 2 and 3 are drawings that diagrammatically show other examples of the all-solid-state battery of the present invention. Fig. 2 is a plan view of the all-solid-state battery, and Fig. 3 is a cross-sectional view taken along line II in Fig. 2.

[0101] The all-solid-state battery 100 shown in Figures 2 and 3 houses an electrode assembly 200 consisting of a positive electrode for the all-solid-state battery of the present invention, a solid electrolyte layer, and a negative electrode in a laminate film exterior 500 consisting of two sheets of metal laminate film, and the laminate film exterior 500 is sealed at its outer periphery by heat-sealing the upper and lower metal laminate films. In Figure 3, in order to avoid complicating the drawing, the layers constituting the laminate film exterior 500 and the positive electrode, negative electrode, and separator constituting the electrode assembly are not shown separately.

[0102] The positive electrode of the electrode body 200 is connected to a positive electrode external terminal 300 within the battery 100, and although not shown, the negative electrode of the electrode body 200 is also connected to a negative electrode external terminal 400 within the battery 100. One end of the positive electrode external terminal 300 and the negative electrode external terminal 400 is drawn out to the outside of the laminate film exterior body 500 so that they can be connected to an external device or the like.

[0103] The form of the all-solid-state battery may be one having an exterior body composed of an exterior can, a sealing can, and a gasket as shown in FIG. 1, that is, one generally referred to as a coin-type battery or a button-type battery, or one having an exterior body composed of a resin film or a metal-resin laminate film as shown in FIGS. 2 and 3, or one having an exterior body having a metallic, bottomed, tubular (cylindrical or rectangular) exterior can and a sealing structure that seals the opening of the can.

[0104] The all-solid-state battery of the present invention can be used in the same applications as conventionally known primary batteries and secondary batteries, but since it has a solid electrolyte instead of an organic electrolyte, it has excellent heat resistance and can be preferably used in applications where it is exposed to high temperatures. In addition, the positive electrode for an all-solid-state battery of the present invention can constitute the all-solid-state battery of the present invention. EXAMPLES

[0105] The present invention will be described in detail below with reference to examples, although the present invention is not limited to the following examples.

[0106] Example 1 <Preparation of positive electrode> The average particle size ra is 5 μm and the surface is LiNbO 3 A layer of LiCo 0.98 Al 0.01 Mg 0.01 O 2 The primary particles (positive electrode active material) and the sulfide-based solid electrolyte (Li 6 P.S. 5 The positive electrode mixture was prepared by mixing LiCo (LiCo 2 Cl) and acetylene black (conductive additive) in a mass ratio of 65:32:3 and thoroughly kneading the mixture. Next, 75 mg of the positive electrode mixture was placed in a powder molding die having a diameter of 7.5 mm and pressure molding was performed using a press machine to prepare a positive electrode made of a cylindrical positive electrode mixture compact. 0.98 Al 0.01 Mg 0.01 O 2 Surface of LiNbO 3 The amount of the layer consisting of LiCo 0.98 Al0.01 Mg 0.01 O 2 : 1 part by mass per 100 parts by mass.

[0107] <Formation of solid electrolyte layer> Next, 9.6 mg of the same sulfide-based solid electrolyte used in producing the positive electrode was placed on the positive electrode mixture compact in the powder molding die, and pressure molding was performed using a press to form a solid electrolyte layer on the positive electrode mixture compact, thereby obtaining a laminate of the positive electrode and the solid electrolyte layer.

[0108] <Preparation of negative electrode> The negative electrode was made by stacking metallic Li foil and metallic In foil formed into a cylindrical shape.

[0109] <Battery assembly> The negative electrode was placed on the inner bottom surface of a stainless steel sealed can with a polypropylene ring gasket fitted in, with the metal In foil facing the inner surface of the can. Next, the laminate of the positive electrode and the solid electrolyte layer was stacked so that the solid electrolyte layer was on the negative electrode side, and then a stainless steel outer can was placed over it. The open end of the outer can was then crimped inward to seal, forming a laminated electrode body consisting of the positive electrode, the solid electrolyte layer, and the negative electrode, and producing an all-solid-state battery with a diameter of approximately 9 mm.

[0110] Example 2 The positive electrode active material is LiNbO 3 A layer of LiCo 0.98 Al 0.01 Mg 0.01 O 2 Primary particles (surface LiNbO 3 The amount of the layer consisting of LiCo 0.98 Al 0.01 Mg 0.01 O 2 The solid electrolyte was changed to Li with an average particle size rs of 0.9 μm. 6 P.S. 5A positive electrode made of a positive electrode mixture compact was produced in the same manner as in Example 1 except for changing to Cl, and an all-solid-state battery was produced in the same manner as in Example 1 except for using this positive electrode.

[0111] Example 3 The solid electrolyte is Li with an average particle size rs of 0.4 μm. 6 P.S. 5 A positive electrode made of a positive electrode mixture compact was produced in the same manner as in Example 2, except that Cl was used, and an all-solid-state battery was produced in the same manner as in Example 1, except that this positive electrode was used.

[0112] Example 4 The positive electrode active material is LiNbO 3 A layer of LiCo 0.98 Al 0.01 Mg 0.01 O 2 Primary particles (surface LiNbO 3 The amount of the layer consisting of LiCo 0.98 Al 0.01 Mg 0.01 O 2 The solid electrolyte was changed to Li with an average particle size rs of 2 μm. 6 P.S. 5 A positive electrode made of a positive electrode mixture compact was produced in the same manner as in Example 1 except for changing to Cl, and an all-solid-state battery was produced in the same manner as in Example 1 except for using this positive electrode.

[0113] Example 5 The positive electrode active material is LiNbO 3 A layer of LiCo 0.98 Al 0.01 Mg 0.01 O 2 Primary particles (surface LiNbO 3 The amount of the layer consisting of LiCo 0.98 Al 0.01 Mg 0.01 O 2A positive electrode made of a positive electrode mixture molded body was produced in the same manner as in Example 3, except for changing the ratio of the positive electrode mixture to the positive electrode mixture molded body (1 part by mass per 100 parts by mass). An all-solid-state battery was produced in the same manner as in Example 1, except for using this positive electrode.

[0114] Comparative Example 1 The positive electrode active material is LiNbO 3 A layer of LiCo 0.98 Al 0.01 Mg 0.01 O 2 Primary particles (surface LiNbO 3 The amount of the layer consisting of LiCo 0.98 Al 0.01 Mg 0.01 O 2 A positive electrode made of a positive electrode mixture molded body was produced in the same manner as in Example 1, except for changing the ratio of the positive electrode mixture to the positive electrode mixture molded body (1 part by mass per 100 parts by mass). An all-solid-state battery was produced in the same manner as in Example 1, except for using this positive electrode.

[0115] Comparative Example 2 The positive electrode active material is LiNbO 3 A layer of LiCo 0.98 Al 0.01 Mg 0.01 O 2 Primary particles (surface LiNbO 3 The amount of the layer consisting of LiCo 0.98 Al 0.01 Mg 0.01 O 2 A positive electrode made of a positive electrode mixture molded body was produced in the same manner as in Example 1, except for changing the ratio of the positive electrode mixture to the positive electrode mixture molded body (1 part by mass per 100 parts by mass). An all-solid-state battery was produced in the same manner as in Example 1, except for using this positive electrode.

[0116] Comparative Example 3 The solid electrolyte is Li with an average particle size rs of 0.2 μm. 6 P.S. 5 A positive electrode made of a positive electrode mixture compact was produced in the same manner as in Example 1 except for changing to Cl, and an all-solid-state battery was produced in the same manner as in Example 1 except for using this positive electrode.

[0117] Comparative Example 4 The solid electrolyte is Li with an average particle size rs of 3 μm. 6 P.S. 5 A positive electrode made of a positive electrode mixture compact was produced in the same manner as in Example 1 except for changing to Cl, and an all-solid-state battery was produced in the same manner as in Example 1 except for using this positive electrode.

[0118] Comparative Example 5 The positive electrode active material is LiNbO 3 A layer of LiCo 0.98 Al 0.01 Mg 0.01 O 2 Primary particles (surface LiNbO 3 The amount of the layer consisting of LiCo 0.98 Al 0.01 Mg 0.01 O 2 The solid electrolyte was changed to Li with an average particle size rs of 0.3 μm. 6 P.S. 5 A positive electrode made of a positive electrode mixture compact was produced in the same manner as in Example 1 except for changing to Cl, and an all-solid-state battery was produced in the same manner as in Example 1 except for using this positive electrode.

[0119] Comparative Example 6 The positive electrode active material is LiNbO 3 A layer of LiCo 0.98 Al 0.01 Mg 0.01 O 2 Primary particles (surface LiNbO 3 The amount of the layer consisting of LiCo 0.98 Al 0.01 Mg 0.01 O 2 The solid electrolyte was changed to Li with an average particle size rs of 20 μm. 6 P.S. 5 A positive electrode made of a positive electrode mixture compact was produced in the same manner as in Example 1 except for changing to Cl, and an all-solid-state battery was produced in the same manner as in Example 1 except for using this positive electrode.

[0120] Comparative Example 7 The positive electrode active material is LiCo with an average particle size ra of 5 μm. 0.98 Al 0.01 Mg 0.01 O 2 Primary particles (LiNbO 3 A positive electrode made of a positive electrode mixture molded body was produced in the same manner as in Example 1, except for changing the positive electrode mixture molded body to one that does not have a layer made of the positive electrode mixture molded body, and an all-solid-state battery was produced in the same manner as in Example 1, except for using this positive electrode.

[0121] Comparative Example 8 The positive electrode active material is LiNbO 3 A layer of LiCo 0.98 Al 0.01 Mg 0.01 O 2 Secondary particles (LiNbO 3 The amount of the layer consisting of LiCo 0.98 Al 0.01 Mg 0.01 O 2 A positive electrode made of a positive electrode mixture molded body was produced in the same manner as in Example 1, except for changing the ratio of the positive electrode mixture to the positive electrode mixture molded body (1 part by mass per 100 parts by mass). An all-solid-state battery was produced in the same manner as in Example 1, except for using this positive electrode.

[0122] The load characteristics of the all-solid-state batteries of the Examples and Comparative Examples were evaluated by the following method.

[0123] For each of the all-solid-state batteries of the Examples and Comparative Examples, a constant current charge was performed at a current value of 0.5 C until the voltage reached 4.0 V, followed by constant voltage charge until the current value reached 0.02 C, and then discharged at a current value of 0.05 C until the voltage reached 2.6 V, and the initial capacity was measured.

[0124] After the initial characteristic evaluation, the 0.5 C discharge capacity of each battery was measured by charging and discharging it under the same conditions as when the initial capacity was measured, except that the current value during discharge was changed to 0.5 C. The 0.5 C discharge capacity of each battery was then divided by the initial capacity to obtain a capacity retention rate, which was expressed as a percentage, and the load characteristics of each battery were evaluated.

[0125] These results, together with the configurations of the positive electrode active material and solid electrolyte in the positive electrode, are shown in Table 1. Note that the average particle size of the positive electrode active material in Comparative Example 8 is the value of the secondary particles, and in Table 1, this value is shown in the "ra" column, and the ratio of the average particle size of this secondary particle to the average particle size of the solid electrolyte is shown in the "ra / rs" column.

[0126] [Table 1]

[0127] As shown in Table 1, the all-solid-state batteries of Examples 1 to 5, which used a positive electrode active material made of primary particles having a reaction suppression layer on the surface and had a positive electrode made of a positive electrode mixture molded body with an appropriate ratio ra / rs of the average particle diameter ra of the positive electrode active material to the average particle diameter rs of the solid electrolyte, had high capacity retention rates during the load characteristic evaluation and excellent load characteristics.

[0128] In contrast, the batteries of Comparative Examples 1 to 6, which have a positive electrode made of a positive electrode mixture molded body in which the positive electrode active material and solid electrolyte were combined so as to give an unsuitable ra / rs value, the battery of Comparative Example 7, which has a positive electrode made of a positive electrode mixture molded body using a positive electrode active material that does not have a reaction suppression layer on its surface, and the battery of Comparative Example 8, which has a positive electrode made of a positive electrode mixture molded body using a positive electrode active material present in the form of secondary particles, had lower capacity retention rates during the load characteristic evaluation and inferior load characteristics compared to the batteries of the Examples. [Explanation of symbols]

[0129] 1,100 All-solid-state secondary battery 10 positive electrode 20 negative electrode 30 Solid electrolyte layer 40 Outer can 50 sealed cans 60 Gasket 200 Electrode body 300 Positive external terminal 400 Negative external terminal 500 Laminated film exterior

Claims

1. The battery has a positive electrode active material made of primary particles and a positive electrode mixture molded body containing a solid electrolyte, the positive electrode active material has a reaction suppression layer on a surface thereof for suppressing a reaction between the positive electrode active material and the solid electrolyte; a ratio ra / rs of an average particle diameter ra of the positive electrode active material to an average particle diameter rs of the solid electrolyte is 2 or more and 20 or less (excluding the case where it is 4.25); The positive electrode for an all-solid-state battery, wherein the ra is 2 to 30 μm.

2. The positive electrode for an all-solid-state battery according to claim 1, wherein the solid electrolyte has an average particle size rs of 0.4 to 2.5 μm.

3. 3. The positive electrode for an all-solid-state battery according to claim 1, wherein the reaction suppression layer contains Nb oxide.

4. The positive electrode active material is represented by the following general formula (1): Love 1-a-b-c Al a M 1 b M 2 c O 2 (1) [In the general formula (1), M 1 represents at least one element selected from the group consisting of Mg, Ni and Na; M 2 is at least one element selected from the group consisting of Mn, Fe, Cu, Zr, Ti, Bi, Ca, F, P, Sr, W, Ba, Nb, Si, Zn, Mo, V, Sn, Sb, Ta, Ge, Cr, K, S, and Er, and 0<a<0.1, 0<b<0.1, a+b<0.1, 0≦c. The positive electrode for an all-solid-state battery according to any one of claims 1 to 3, containing a lithium-cobalt composite oxide (A) represented by the following formula:

5. An all-solid-state battery having a positive electrode, a negative electrode, and a solid electrolyte layer interposed between the positive electrode and the negative electrode, An all-solid-state battery comprising the positive electrode for an all-solid-state battery according to any one of claims 1 to 4 as the positive electrode.

Citation Information

Patent Citations

  • Fuel-solid lithium secondary battery

    JP1996195219A

  • Lithium ion secondary battery

    JP2016001596A

  • Lithium ion secondary battery

    JP2016062683A

  • Positive electrode for solid-state batteries, solid-state battery and method for producing solid-state battery

    WO2019150559A1